(untitled) (Web of Teachers: Inderscience Research, 2024)
Written monuments in the Sugdian language of the early Middle Ages, including the documents of Mugh Mountain, contain important information not only about the political relations of the Sughd oasis, but also about a number of countries and regions of Central Asia and the political-diplomatic relations established between them. It is important that the information on political relations in these documents is consistent with the information in the Chinese and Arab sources of that period, which increases their importance even more.